Associations Between microRNA-related Genetic Polymorphisms and Clinical Response to Methotrexate in Chinese Rheumatoid Arthritis Patients - Wen, Qin-Wen; Chen, Chong-Jing; Zhang, Han-Qing; Yu, Hang; Zeng, Zhen; Jin, Ting; Wang, Ting-Hui; Qin, Wen; Huang, Hua; Wu, Xiu-Di; Cen, Han (Current Pharmaceutical Design, 2022)
Background: Emerging evidence indicates that microRNA (miRNA)-related genetic polymorphisms are strongly involved in the post-transcriptional regulation of the expression of pharmacokinetics and pharmacodynamics- related genes, therefore contributing to the genetic variability of drug response. Objective: To investigate the associations of miRNA-related genetic polymorphisms, including miRNA-5189 rs562929801, miRNA-595 rs4909237, SLCO1A2 rs4149009 and MTHFR rs3737966, and clinical response to methotrexate in Chinese rheumatoid arthritis patients. Methods: One hundred patients treated with MTX for approximately 3 months were prospectively followed up to evaluate the clinical response according to European League Against Rheumatism (EULAR) good and moderate response, disease activity score in 28 joint counts - erythrocyte sedimentation rate (DAS28-ESR) low disease activity (LDA) and remission (REM), change in DAS28-ESR (ΔDAS28-ESR) and ΔDAS28-ESR > 0.6. Genetic polymorphisms were genotyped utilizing the HI-SNP technology. Results: Of the 100 patients with a mean age of 52.23 ± 12.71 years, 81 patients were female (81.00%). After adjusting potential confounders, the major allele of miRNA-5189 rs562929801 was found to be significantly associated with EULAR response (A/A + A/G versus G/G, RR = 0.81, 95% CI = 0.67-0.99, P = 0.04) and ΔDAS28-ESR > 0.6 under dominant model (A/A + A/G versus G/G, RR = 0.83, 95% CI = 0.71-0.98, P = 0.03). However, nonsignificant evidence was detected for the remaining three miRNA-related genetic polymorphisms in neither univariable analysis nor multivariable analysis. Conclusion: Our results indicated that miRNA-5189 rs562929801 was significantly associated with clinical response to MTX, and this association warrants further replication studies with larger sample sizes.
Keywords: MTHFR